Authority And Responsibility Of A Notary In Making A Financing Agreement At A Sharia Banks In The Form Of A Notary Deed - Lubis, Muhammad Syukran Yamin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The development of the Islamic banking industry has contributed greatly to the economy in the city of Medan. The purpose of this study is to analyze the role of notaries in implementing Islamic financing agreements in the form of notarial deeds in the city of Medan. To analyze the legal certainty of Islamic financing agreements in the form of notarial deeds in the city of Medan. To analyze the reconstruction of the implementation of Islamic financing agreements in the form of notarial deeds in the city of Medan. This type of research is normative juridical, namely research obtained from the results of data collection through literature studies. The data source in this study is secondary data, namely data obtained from literature searches, which come from primary legal materials, secondary legal materials and tertiary legal materials. Based on the research results, it can be understood that the Authority of Notaries in Making Financing Contracts at Islamic Banks in the Form of Notarial Deeds is based on their authority as regulated in the provisions of Article 15 paragraph (1) of the Notary Law. In making financing contracts, notaries follow all provisions of laws and regulations regarding the making of Notarial deeds and all the pillars and requirements for making contracts, and pay attention to the contents of the deed so that they can avoid anything prohibited by Islamic law. Meanwhile, the form of responsibility of notaries for their mistakes in making financing contracts for Islamic banking is in the form of responsibility in terms of civil law, criminal law, administrative law and even responsibility in terms of Islamic law